Psychological Impact Of Kidnapping On Social Reintegration And Academic Pursuits Of Female Undergraduates In Zamfara State - Isma'il, Akilu; Ibrahim, Halimat Bashir (Academic Journal of Psychology and Counseling, 2025)
Kidnapping and banditry have become pervasive in northern Nigeria, severely disrupting the lives of vulnerable communities including students in both pre-tertiary and tertiary institutions, particularly Zamfara State. However, research on their psychological impact on female undergraduate students is lacking. To fill this gap, this study investigated the psychological impact of kidnapping on female undergraduate students in Zamfara State, focusing on their social reintegration and academic pursuits. The study adopted a qualitative research design. Seven female undergraduates of Federal University Gusau who had recently been released after prolonged captivity participated in the study. A combination of purposive and snowball sampling techniques was used to select participants based on availability, willingness, and ability to provide detailed accounts. Data was collected through structured interviews. Thematic analysis revealed profound psychological trauma, including symptoms of post-traumatic stress disorder (PTSD), anxiety, and depression. Social reintegration challenges found in the study include stigmatization and alienation, while academic difficulties involve concentration, memory issues, and decreased motivation. The study recommends implementing comprehensive psychological support programs within educational institutions located in high-risk locations like Zamfara State, including professional counseling and peer support groups, to address the long-term psychological effects and facilitate better social and academic reintegration of the victims.